2019
DOI: 10.3889/oamjms.2019.617
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Accuracy of Radiography and Sonography in Detection of Knee Osteoarthritis: A Diagnostic Study

Abstract: BACKGROUND: Knee osteoarthritis (OA) is the most common degenerative disorder occurring in elderly people. Radiography and sonography are convenient techniques to detect diverse pathological features of knee OA. BACKGROUND: Knee osteoarthritis (OA) is the most common degenerative disorder occurring in older people. Radiography and sonography are convenient techniques to detect diverse pathological features of knee OA. AIM: The aim of the present study was to evaluate the diagnostic efficacy of radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Novel techniques taking knee articular motion into consideration was shown to be more valid to significantly decrease false-negative diagnoses compared with fixed-angle transverse scanning [34] and it can be considered to be incorporated in future work. Also in previous study, ultrasonography has a very poor sensitivity for diagnosing patellar cartilage defect, which was reported to be 0 [17] and this pathology can also cause symptoms of knee derangement [35] and affect sports activity. These might explain the inferior correlation of IKDC-SKR with ultrasonography findings in this tested subject.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Novel techniques taking knee articular motion into consideration was shown to be more valid to significantly decrease false-negative diagnoses compared with fixed-angle transverse scanning [34] and it can be considered to be incorporated in future work. Also in previous study, ultrasonography has a very poor sensitivity for diagnosing patellar cartilage defect, which was reported to be 0 [17] and this pathology can also cause symptoms of knee derangement [35] and affect sports activity. These might explain the inferior correlation of IKDC-SKR with ultrasonography findings in this tested subject.…”
Section: Discussionmentioning
confidence: 93%
“…When it comes to sideline sports medicine, soft tissue ultrasonography bares advantages of high safety, non-radiative, highly portable, relatively cheap in price and the ability to allow dynamic testing at the field. For many common knee disorders mentioned above, research has shown good sensitivity and excellent specificity of ultrasonographic diagnosis confirmed with magnetic resonance imaging (MRI) [17]. Although recent study demonstrated excellent precision of ultrasonography as compared to MRI in the diagnosis of ACL and PCL tears and serve as immediate diagnosis in patients with acute knee trauma [18], we did not include ACL/PCL screening in our protocol since these injury is less likely to be "unknown" because of the injury almost always occur in an acute scenario.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Additionally, our agreement estimates may be influenced by extraneous sources of error such as the time of day or the day of week of ratings, which may underestimate the correspondence between assessments. Our validity study lacks a gold standard comparator, although it has been previously reported that MRI and US measures of joint effusion, joint thickness, osteophyte, and meniscal pathology have excellent agreement (40). It has also been shown that US performs better or equal to radiography in measuring osteophytes, meniscal pathology, and cartilage damage (10).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of medical imaging, 3 various technologies, such as magnetic resonance imaging (MRI), 1,7,8 computed tomography (CT) scan, 9,10 ultrasound, 11,12 and plain radiographs (X‐rays) are available for the diagnosis of KOA. The advantages like cost‐effectiveness, less exposure to radiation, and easy availability, make X‐ray the versatile and most widely used imaging modality for the diagnosis of knee OA 13–15 …”
Section: Introductionmentioning
confidence: 99%